2018
DOI: 10.1155/2018/8528315
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Atropine Eye Drops on Choroidal Thinning Induced by Hyperopic Retinal Defocus

Abstract: Purpose. To investigate the effects of atropine on choroidal thinning induced by hyperopic retinal defocus. Methods. Ten young adults with myopia (−1.00 D to −5.00 D) viewed a video at 6 metres for 60 minutes on successive days. On day 1, one eye (control) was distance corrected with a contact lens; the other (experimental) eye wore a contact lens imposing 2.00 D of hyperopic retinal defocus. Sub-and perifoveal choroidal thickness (SFCT, PFCT) were monitored with optical coherence tomography. On day 2, the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 28 publications
(39 reference statements)
4
32
0
Order By: Relevance
“…administered 0.5 per cent atropine 22 hours prior to exposing subjects to −2.00 D hyperopic blur and found that prior atropine use negated the thinning effect of the hyperopic blur. Sander et al used two per cent homatropine in combination with ±3.00 D of blur and found that after 60 minutes, the homatropine had eliminated the thinning effect of minus blur, similar to the longer‐term findings of Chiang and Phillips . These findings suggest that a muscarinic pathway may be involved in the eye’s response to minus blur.…”
Section: Changes In the Choroid Associated With Environmental Factorsmentioning
confidence: 79%
See 1 more Smart Citation
“…administered 0.5 per cent atropine 22 hours prior to exposing subjects to −2.00 D hyperopic blur and found that prior atropine use negated the thinning effect of the hyperopic blur. Sander et al used two per cent homatropine in combination with ±3.00 D of blur and found that after 60 minutes, the homatropine had eliminated the thinning effect of minus blur, similar to the longer‐term findings of Chiang and Phillips . These findings suggest that a muscarinic pathway may be involved in the eye’s response to minus blur.…”
Section: Changes In the Choroid Associated With Environmental Factorsmentioning
confidence: 79%
“…Combinations of anti‐muscarinics and optical blur have been studied. Chiang and Phillips . administered 0.5 per cent atropine 22 hours prior to exposing subjects to −2.00 D hyperopic blur and found that prior atropine use negated the thinning effect of the hyperopic blur.…”
Section: Changes In the Choroid Associated With Environmental Factorsmentioning
confidence: 99%
“…Studies in a range of species show that a thinning or thickening of the choroid in response to hyperopic or myopic defocus results in a rapid movement of the retina towards the defocused image plane, followed by alterations in scleral growth that eventuates in the development of experimental myopia or hyperopia, respectively . In humans, short‐term exposure to full‐field myopic and hyperopic defocus in both children and adults has also elicited a transient increase or decrease in choroidal thickness respectively, implying that the choroid may contribute to the mechanisms involved in the longer‐term development of refractive errors in humans …”
Section: Introductionmentioning
confidence: 99%
“…To date, human studies have only examined foveal or nasal and temporal parafoveal choroidal thickness changes in response to full‐field defocus and suggest that the defocus mediated changes in choroidal thickness occur uniformly across the central macular area. However, studies in chicks have revealed that greater changes in choroidal thickness occur centrally, rather than peripherally, in response to full‐field optical defocus .…”
Section: Introductionmentioning
confidence: 99%
“…8 Evidence from animal studies indicates that atropine acts via a non-accommodative mechanism, 9 and in humans atropine eye drops cause thickening of the choroid 10 and also abolish the choroidal thinning normally associated with exposing the retina to hyperopic defocus. 11 Atropine also reduces the refractive error changes associated with myopia progression in concentrations as low as 0.01% (which produce negligible mydriasis and cycloplegia). 6 Support for a retinal site of action comes from the finding that retinal dopamine levels, which are reduced in experimentally induced myopia in chicks, are increased with intravitreal injection of atropine that subsequently triggers spreading depression effects in the retina.…”
mentioning
confidence: 99%